Keberkesanan aplikasi TMK dalam meningkatkan penguasaan kemahiran membaca murid: satu kajian kes (Jurnal Bahasa, 2022)
This study was undertaken to evaluate the effectiveness of Information and Communication Technology (ICT) applications in enhancing students’ reading skills, interest and involvement in the process of teaching and learning. The study was undertaken using pre- and posttesting to gauge reading skills and teacher observation instruments to measure students’ interest and involvement. Two methods of teaching and learning were used in this study, the Stand Alone method, with ICT facilities equivalent to those of the computer lab and school access, and the Classroom method. Reading skills were imparted to students through self -enrichment and teacher focus. It was found that student interest was high for teaching and learning using ICT, and the Stand Alone method compared to the Classroom method. Student participation was also higher in teaching and learning when ICT was used and there was no difference between observations for Stand Alone method and Classroom method. Overall there was a general improvement in reading proficiency of students.